Low-grade mucinous neoplasm originating from intestinal duplication: a case report and review of the literature - Huihui Yin; Jie Yu; Yunzhao Chen (World Journal of Surgical Oncology)
Abstract Background Low-grade mucinous neoplasms typically originate from the appendix and are characterized by a lining of low-grade mucus-secreting columnar epithelial cells and smooth muscle. However, atypical origins can occur, as demonstrated in this case report. Case presentation We present a case involving a 33-year-old male who, upon physical examination, was found to have an abdominal mass. A computed tomography (CT) scan revealed a cystic mass located between the pancreatic tail and the adjacent bowel duct, with significant enhancement of the cyst wall observed on contrast-enhanced imaging. The patient subsequently underwent laparoscopic surgical resection of the mass, and the resected specimen was sent for pathological evaluation. The pathology results were consistent with the histological morphology and immunohistochemical characteristics of low-grade mucinous tumors arising from intestinal duplication. Three and a half years post-resection, the patient returned for a follow-up examination, during which abdominal CT and blood tumor markers indicated no signs of tumor recurrence. Conclusions While low-grade mucinous tumors predominantly originate from the appendix, this case illustrates an unusual occurrence of such neoplasms arising from intestinal duplication. This report aims to enhance clinical awareness of low-grade mucinous tumors originating from intestinal duplication, thereby improving the rates of preoperative diagnosis and reducing instances of misdiagnosis.